Does market competition motivate corporate social responsibility? Insight from Malaysia - Kontesa, Maria; Brahmana, Rayenda Khresna; Memarista, Gesti (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study aims to examine the role of product market competition on Corporate Social Responsibility (CSR) by engaging altruism and utilitarianism views. Using dynamic Generalized Method of Moment panel regression for 524 Malaysian non-financial industry listed companies from 2010 to 2016, we find that firms in a more competitive environments increase their CSR activities. We interpret these results as evidence that CSR is strategically chosen by firms not for the societal benefits, but more on business as usual; a support for utilitarianism view, i.e profit maximizations. It explains the rationale that CSR activities are less employed in a more monopolistic or oligarchic industry. Practically, this study suggests that the CSR activities are forced by market competition. Firms in a more competitive market need CSR as their non-market strategies.